Factors associated with body image in Physical Education students Fatores associados à imagem corporal em estudantes de Educação Física - Da Silva T.R. (2011)
The aim of this study was to investigate factors associated with body image in physical education students. 230 students answered a questionnaire with body image and physical activities habits questions. Anthropometrics evaluations were taken. Adjusted analyses with underweight and overweight dissatisfactions were performed. 62.8% of males and 67% of females showed body dissatisfaction. The dissatisfaction because they regarded themselves as being too thin was 2.71 (CI95%: 1.47-4.99) fold higher in males and the dissatisfaction because they perceived themselves as overweight was 2.22 (CI95%: 1.40-3.54) fold higher in females. Due to high body dissatisfaction prevalence identified, we suggest the higher attention about body image and beauty standards questions in curricular activities. This would enable the better professional performance with body dissatisfaction and distorted body image groups common in schools and academies.